Cooperative Integrated Reading and Composition (CIRC) Implementation to Enhance Student Learning Outcomes - Anwar Sewang; Muhammad Aswad (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to determine the increase in learning results of Islamic Education in reading material using the Cooperative Integrated Reading and Composition (CIRC) learning model. This research is Classroom Action Research involves planning, implementing, observing, and reflecting. This Class Action Research procedure is planned for cycles I and II. Cycle I consists of four meetings, and cycle II consists of four sessions.  Meetings 1 to 3 carried out the teaching and learning process and meeting four carried out learning outcomes tests through descriptive data analysis. This research is designed using the CIRC learning model. The results showed that the average value of students' learning outcomes of grade VII Bilingual 1 SMP Negeri 6 Sengkang increased from cycle I to cycle II, i.e., from 78.30 to 83.96. In process one, the complete student is 73,91% or 17 students. While in cycle II, the percentage of student mastery increased to 95.65% or 22 students. Based on the result of the research, it can be concluded that using the CIRC learning model can improve the learning result of PAI of the law reading material. CICR models can help the learning process more optimally because it is able to increase the activeness of student learning outcomes as cognitive and affective terms. In the process of learning pleasant classroom conditions able to support students in receiving material lessons and models of CIRC with gift-giving can be used as one of the learning models in learning reading comprehension.